Potential application of nanodelivery systems targeting ELAVL1 in prostate cancer treatment - Min, Shasha; Guo, Mengmeng; Du, Jianuo; Chen, Jiaohuang; Shen, Yanting; Yuan, Fuwen; Wang, Zhong; Cai, Zhonglin (Frontiers in Oncology, 2025)
IntroductionProstate cancer (PCa) is one of the most common malignant tumors in men, with increasing incidence and mortality rates, and its treatment still faces many challenges and unmet needs. ELAVL1 (human antigen R, HuR) is an RNA-binding protein that plays a crucial role in the development and progression of various cancers. Studies have shown that ELAVL1 is highly expressed in PCa and that inhibiting its expression significantly reduces prostate cell proliferation and metastasis. However, the clinical application of ELAVL1-targeting therapies remains limited by the lack of effective delivery strategies. In this context, recent advances in nanodelivery systems offer promising solutions, providing both enhanced targeting efficiency and insights for future prostate cancer treatment strategies.ObjectiveThis review aims to explore the potential of ELAVL1-targeted therapy based on nanodelivery systems in PCa, analyze its advantages and challenges, and provide insights into future research directions.MethodsA systematic review of recent literature summarizing the expression characteristics and biological functions of ELAVL1 in PCa was conducted. Additionally, the advantages, challenges, and applications of various nanomaterials in cancer therapy are discussed.ResultsNanodelivery systems have shown significant potential in the treatment of prostate cancer.